Tillage and Nitrogen Placement Effects on Yields in a Short-Season Corn/Wheat/Double-Crop Soybean Rotation - D. W. Sweeney; Dorivar Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2018)
Many crop rotation systems are used in southeastern Kansas. This experiment was designed to determine the long-term effect of selected tillage and N fertilizer placement options on yields of short-season corn, wheat, and double-crop soybean in a rotation.
Keywords: Tillage; no-till; nitrogen placement; corn; wheat; soybean